2005
DOI: 10.1088/0953-8984/17/38/009
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for atomic scale disorder in indium nitride from perturbed angular correlation spectroscopy

Abstract: The crystal lattice of bulk grains and state-of-the-art films of indium nitride was investigated at the atomic scale with perturbed angular correlation spectroscopy using the 111 In/Cd radioisotope probe. The probe was introduced during sample synthesis, by diffusion and by ion implantation. The mean quadrupole interaction frequency ν Q = 28 MHz was observed at the indium probe site in all types of indium nitride samples with broad frequency distributions. The observed small, but non-zero, asymmetry parameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
3
4
0
Order By: Relevance
“…At room temperature Dogra et al [22] observed a QIF of ν Q = 28 MHz at the cation site in InN which is consistent with measurements for other nitrides. However, it was not possible to anneal the implantation damage completely, which is attributed to inherent defects in the InN lattice.…”
Section: Defect and Diffusion Forum Vol 311supporting
confidence: 81%
“…At room temperature Dogra et al [22] observed a QIF of ν Q = 28 MHz at the cation site in InN which is consistent with measurements for other nitrides. However, it was not possible to anneal the implantation damage completely, which is attributed to inherent defects in the InN lattice.…”
Section: Defect and Diffusion Forum Vol 311supporting
confidence: 81%
“…The perturbed angular correlation spectroscopy of indium nitride carried out in this work utilizing the radioisotope 111 In/Cd led to the discovery of n ¼ 28 MHz as the interaction frequency for this probe [16,17]. This is consistent with measurements for gallium nitride (6 MHz) and aluminium nitride (32 MHz) and also with expectation due to the generally low electric field gradient of wurtzite lattices.…”
Section: Article In Presssupporting
confidence: 81%
“…The bulk grains were doped during synthesis, whereas the probe was ion-implanted into RPECVD-and MBE-grown films after growth [16,17]. The 111 In/Cd radioisotope is particularly suited to the study of indium nitride since it can be expected that the atoms occupy indium lattice sites prior to the radioactive decay of their nucleus.…”
Section: Experimental Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…These results revealed the formation of Pd-V and Pd-B defect complexes, respectively, in highly doped n-and p-Si. Figure 3d shows the PAC spectrum of polycrystalline synthesized InN, where the leastsquares fitted parameters reveal the presence of In 2 O 3 contents in the sample; 43 the starting materials for synthesis was In 2 O 3 . Besides, we observed an interaction frequency of 28 MHz having a broad distribution with a small nonzero value of asymmetry parameter at the indium site in an InN crystal lattice.…”
Section: Local Structure Around Probes: Site Allocationsmentioning
confidence: 99%